Bush meets hotelling: Effects of improved renewable energy technology on greenhouse gas emissions - Michael Hoel (Fondazione Eni Enrico Mattei (FEEM), 2009)
Fossil fuels are non-renewable carbon resources, and the extraction path of these resources depends both on present and future demand. When this Hotelling feature is taken into consideration, the whole price path of carbon fuel will shift downwards as a response to the reduced cost of the renewable substitute. An implication of this is that greenhouse gas emissions in the near future may increase as a response to the reduced cost of the renewable substitute. If this is the case, increased climate costs may outweigh the benefits of reduced costs of a substitute, thus reducing overall social welfare.
Keywords: Q30; Q42; Q5; 330; Climate Change; Exhaustible Resources; Renewable Energy